A Reader in art librarianship - Pacey, Philip; International Federation of Library Associations and Institutions (München ; New York : K.G. Saur, 1985)
The readings are organized in four major parts. The first focuses on the art librarian: why did the need for this specialized professional arise, how did the profession become established, what kind of training does it require? The second and longest part examines in four sections the users of art libraries: art historians and curators, artists and art students, designers, and the public. The third part examines the visual nature of art and the librarian's challenge to organize and make this material accessible: the methods used for books have hampering limitations for visual research. The fourth part, "Cooperation and Association," acknowledges that art objects, the primary focus of study, are dispersed all over the world and so is the documentation available for these objects.
Includes bibliographical references.
aia 16/06/2017
Loans
Keywords: Art libraries